184k views
4 votes
Solve for y.
ln(2y−1)=3

Answer y=(e^3+1/2)

for future reference

User Yoonhee
by
6.5k points

2 Answers

0 votes

Answer:

The correct answer is indeed y =
(e^3+1)/(2)

Explanation:

I also took the test!

User PermaFrost
by
5.2k points
5 votes

Answer:

The correct answer should be:


y=(1)/(2)(e^3+1)\text{ or } y=(e^3)/(2)+(1)/(2)

Explanation:

We have the equation:


\ln(2y-1)=3

Let’s remove the natural logarithm by raising both sides to e. This yields:


e^(\ln(2y-1))=e^3

The left will simplify to:


2y-1=e^3

Add 1 to both sides:


2y=e^3+1

Divide both sides by 2. So, the value of y should be:


y=(1)/(2)(e^3+1)

User Petrnohejl
by
5.4k points